Cold Thermal Energy Storage (CTES) Study In A Hospital Building - Akhmad Faruq Alhikami; Egi Dwi Gusuma; Moh. Fiqi Firmansah; Rusdan Aditya Aji Nugroho; Riswan Sepriyatno (G-Tech: Jurnal Teknologi Terapan, 2024)
This paper studies cold thermal energy storage in a hospital building. There are six CTES strategies to implement in the building includes full storage, levelling storage, partial storage 30%, partial storage 50%, partial storage 70%, and partial storage 90%. The energy consumption, electricity cost and chiller performances are evaluated to find the optimum mode.The results showed that levelling storage found the best mode for new cooling system investment with annual savings up to 10.5%. In addition the energy consumption is considered lower than normal cooling system. The chiller capacity of partial storage 30% is closed to normal cooling, thus this strategy is the best for replacement system with the annual savings up to 13%.